Single ended capacitive self-sensing system for comb drives driven XY nanopositioners - del Corro, Pablo Guillermo (2018)
This paper presents the implementation of a system to capacitively self-sense the position of a comb drive based MEMS XY nanopositioner from a single common node. The nanopositioner was fabricated using the multi-users PolyMUMPs process, on which comb capacitors fringe fields are large and out of plane forces cause considerable deflection. An extensive analysis of the comb-drive capacitance including the levitation effects and its correlation to the measurements is presented. Each axis is independently measured using frequency division multiplexing (FDM) techniques. Taking advantage of the symmetry of the nanopositioner itself, the sensitivity is doubled while eliminating the intrinsic capacitance of the device. The electrical measured noise is 2.5 aF/Hz, for a sensing voltage Vsen = 3Vrms and fsen = 150 kHz, which is equivalent to 1.1 nm/Hz lateral displacement noise. This scheme can also be extended to N-degree of freedom nanopositioners.